SOCIOLOGICAL METHOD IN THE RESEARCH OF THE UKRAINIAN LEGAL THOUGHT - ANDRUSYAK, T. (Ehrlich’s Journal, 2023)
The problem of the formation of the methodology of studying the Ukrainian legal thought – intellectual achievements of previous generations of the Ukrainian people in the law – is reviewed. It is determined, that the precondition of modern Ukrainian jurisprudence is radical rethinking its theoretical and methodological foundations. Based on Ukrainian legal thought it is possible to create a theoretical basis for the formation and development of Ukraine as a nation formed as a result of the Ukrainian people’s right to self-determination. It is proved, that the rejection of ideological dogmas of the Soviet totalitarian regime, rethinking and updating the theoretical heritage of outstanding Ukrainian lawyers, will allow finding adequate answers to modern challenges and create appropriate framework for a comprehensive and effective development of the Ukrainian law. The law and legal opinion as elements of national culture and spiritual heritage of the people, which is inextricably linked to social life that distinguishes them from the law and jurisprudence, which depend on the state and cannot have anything to do with the culture of the people, nor his ideas about right, are being characterized. It is especially important for the Ukrainian people, who in the last century were the part of states that have pursued a policy in its assimilation and denationalization. The necessity of the use of the entire spectrum of sociological approaches and methods for integrated and comprehensive information about the notion of the people about the law, trends in the development of these ideas, and wrought negative impact of the ideology, public policy, current law on legal awareness and legal culture – are being emphasized.